Armies and Ecosystems in Premodern Europe - Govaerts, Sander (Arc Humanities Press, 2021)
Military history; Ecological history; war and the environment; Natural barriers in history; wildlife protection, mosasaur; premodern environmentalism
Keywords: Ecological History; Natural Barriers In History; War And The Environment; Wildlife Protection, Mosasaur; Military History